PRAKTEK MANAJMEN SUMBER DAYA MANUSIA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK SMBC KC MANADO - Boediman, Monique (Universitas Sam Ratulangi, 2026)
This study aims to analyze the influence of human resource management (HRM) practices and job satisfaction on employee performance at PT Bank SMBC Indonesia Tbk, Manado Branch Office. The research method used is quantitative with a Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The research population consists of 50 permanent employees, with a sample of 34 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and processed using the SmartPLS software to test validity, reliability, and relationships among variables. The results indicate that HRM practices have a positive and significant effect on job satisfaction, as well as a positive and significant effect on employee performance. However, job satisfaction does not have a significant effect on employee performance. This finding implies that employee performance improvement is primarily determined by effective HRM practices rather than directly by the level of job satisfaction. The conclusion of this study emphasizes that effective human resource management including proper recruitment systems, relevant training, fair compensation, and objective performance evaluation plays an important role in enhancing employee productivity and performance. Meanwhile, job satisfaction only plays an indirect role in influencing performance. Keywords: Human Resource Management Practice, Job Satisfiction, Employee Performance, SEM-PLS